ANALISIS FAKTOR MENGUASAI ILMU MENDIDIK DALAM MENINGKAT EFEKTIVITAS PEMBELAJARAN PAK OLEH GURU PADA SISWA KELAS VIII SMP NEGERI 2 DOLOKSANGGUL KABUPATEN HUMBANG HASUNDUTAN TAHUN PEMBELAJARAN 2017/2018 - Rika Damayanti Sitorus (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2018)
Abstract This study aims to analysis the Factors Mastering Educational Sciences in Improving the Effectiveness of PAK, with hypothesis Factors Mastering Educational Sciences in Improving the Effectiveness of PAK Learning by teachers in students of Class eigth Junior High School 2 Doloksanggul Year Learning 2017/2018 75% than expected. This research uses descriptive quantitative method, with research population are all students of Class eight Junior which amounted to 261 people and samples taken 20% so that the sample amounted to 52 people. The research instrument is a closed questionnaire. The trial was conducted to 30 students of class eight Junior High School 1 Doloksanggul. Instrument validity test using Pearson Product Correlation Coefficient formula is obtained rcount rtable that is between 0453 s / d 0.740 3.61 thus the instrument is categorized valid. Test Reliability instrument with Formula Alpha formula obtained r11 = 0.95,thus reliable. From the results of data analysis obtained value of Factors Mastering Educational Science in Improving the Effectiveness of PAK = 84.86% is in very good category. Based on t test obtained t count ttable that is 16,578 1.66 thus H0 rejected and Ha accepted that is Factor Mastering Science Educate in Improve Effectiveness of PAK 75% from which is expected to be accepted. Keywords: Factors Mastering Educational Sciences in Improving the Effectiveness